Edukasi Bahaya Limbah Tekstil pada Kesehatan di MAS Al-Washliyah 22 Tembung - Rini Andarwati; Zulfa Ismaniar Fauzi; Irma Noviar (Jurnal Abdi Masyarakat Kita, 2022)
The process of industrial pollution of hazardous and toxic waste (B3), especially in the textile industry, can occur directly or indirectly. The direct process is that the pollutant has a direct impact on poisoning so that it interferes with the health of humans, animals and plants or disrupts the ecological balance of water, air and soil. Indirect process, some chemical substances react in the air, water and soil, causing pollution. Batik waste also contains wax (wax). contains chemical compounds that are harmful to health, starting from itching on the skin, interfering with breathing, digestion and cancer. The purpose of this Community Service is to find out the description of knowledge about waste and its health hazards for students at MAS Al-Washliyah 22 Tembung. The method used is a lecture about the impact of waste and its dangers on health and questions and answers as well as the provision of brochures and measuring instruments using a questionnaire. The results of the measurement of knowledge before education resulted in good knowledge of 60%, 20% enough and 20% less. After good education 75% and 25% enough. There is a significant relationship between before and after education p = 0.000. The conclusion in this service activity is that there is an increase in students' knowledge after education.